ANALISIS SISTEM PEMASARAN GABAH/BERAS (Studi Kasus Petani Padi di Sumatra Utara) - SUPRIATNA, ADE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 1 Februari 2005)
This study was conducted in 2002 and took place in North Sumatra. Districts of Asahan and Simalungun were chosen as area samples. The objectives of study were (i) to describe the channel of rice marketing, (ii) to analyze the components of cost and marketing margin in each agent of marketing link, and (iii) to identify the characteristics and problems in each agent of marketing link. The method of Participatory Rural Appraisal (PRA) was used in this study using Snow Ball Point where the farmers were placed as a start point. Primary data were collected from 50 farmers, 20 traders, 4 village rice mills, and 10 rice consumers. Secondary data were collected from Agriculture office, Institutions for Agricultural Research, and others. The results informed that, in North Sumatra there were found two channels of rice marketing. First, farmers sell direct unhulled rice to collecting merchant then collecting merchant sells them to large merchant (kilang). In kilang, unhulled rice is processed to become hulled rice then sold them to wholesalers and retailer to be sold to consumers. Second, farmers sell unhulled rice to local rice mill. In rice mill, unhulled rice is processed to become hulled rice then sold them to retailer to be sold to consumers. In the first channel, the most marketing margin happened at kilang equal to Rp.216,- with net benefit margin of Rp. 89,-/kg. In the secondary channel the most marketing margin and net benefit margin happened at the village rice mill equal to Rp.210,- and Rp.85,-/kg respectively. Some problems in agents of rice marketing were found especially at the levels of the farmer as rice producer, the collecting merchant, and the local rice mill.
Keywords: Marketing, Rice, North Sumatra